Building a Learning Alliance for Living Labs in Vietnam’s Mekong Delta - Bernardo, Eisen (CGIAR System Organization, 2022)
A collaboration between the CGIAR Initiatives on Asian Mega-Deltas (AMD) and Low-Emission Food Systems (Mitigate+), a Learning Alliance for Living Labs workshop was organized by the International Rice Research Institute (IRRI) in Can Tho City, Vietnam on 6 December 2022 to form a network of diverse stakeholders within the region, that has an interest to address climate-related issues in the Mekong Delta.